Pengembangan Sistem Informasi Manajemen Layanan Konseling FILKOM UB berbasis Mobile - Farhan Fadhillah Djabari; Issa Arwani; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Every individual will not be spared from mental health problems. Therefore, proper handling must be done to prevent more severe problems from occurring. Counseling is one way to avoid these problems. The Faculty of Computer Science is one of the faculties at Brawijaya University with counseling guidance services currently under student services. However, over time there are problems with resources experienced by the counseling guidance service. So the counseling service coordinates with the faculty's student executive board to initiate peer counseling services to increase students' awareness of the importance of mental health and overcome the existing counselor resource problems. In its implementation, the registration, data collection, and reporting process is still carried out separately, which can confuse students using the service. The author offers a solution by utilizing the Flutter framework technology to develop a mobile information system that can help simplify the counseling guidance process. The research was conducted using the waterfall method, from the needs analysis stage to the conclusion. The implementation results in an information system that can handle the administrative process of counseling guidance services. The main features of this information system are counseling guidance scheduling, counselor scheduling, counseling history recording, and writing final counseling reports. Additional features, such as user profiles and notifications when certain activities occur, are also developed. The information system successfully obtained valid results for all test cases using the validity testing method. For usability testing, the system got an average score of 85,47 using the system usability scale method, which is included in the acceptable category on the acceptability range, level B on the grade scale, and excellent rating on the adjective rating. This score considerably increased from the previous system's score, namely 52,75.